2022
DOI: 10.1371/journal.pone.0267757
|View full text |Cite
|
Sign up to set email alerts
|

Winter cover crops increased nitrogen availability and efficient use during eight years of intensive organic vegetable production

Abstract: Efficient use of nitrogen (N) is essential to protect water quality in high-input organic vegetable production systems, but little is known about the long-term effects of organic management on N mass balances. We measured soil N and tabulated N inputs (organic fertilizers, compost, irrigation water, atmospheric deposition, cover crop seed, vegetable transplant plugs and fixation by legume cover crops) and exports in harvested crops (lettuce, broccoli) over eight years to calculate soil surface and soil system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…In an eight-year experiment conducted in Salinas, California, consisting of organic vegetable rotations, a rye-legume cover crop combination also resulted in improved NUE. However, because of the relatively high levels of external inputs, the legume cover crops increased the surplus of N in the system, which may result in environmental losses, while rye was more effective as a cover crop, to minimize N surplus levels from the system [217]. Based on multi-year cover crop evaluations conducted in Japan, including 15 N studies, a combined 2:1 hairy vetch/rye planting ratio was also found to improve the mineralization and synchronization of N release by the individual species, with the N uptake demand of tomato, along with an increase in the overall soil N pool and N cycling [218].…”
Section: System Diversification To Improve Nuementioning
confidence: 99%
“…In an eight-year experiment conducted in Salinas, California, consisting of organic vegetable rotations, a rye-legume cover crop combination also resulted in improved NUE. However, because of the relatively high levels of external inputs, the legume cover crops increased the surplus of N in the system, which may result in environmental losses, while rye was more effective as a cover crop, to minimize N surplus levels from the system [217]. Based on multi-year cover crop evaluations conducted in Japan, including 15 N studies, a combined 2:1 hairy vetch/rye planting ratio was also found to improve the mineralization and synchronization of N release by the individual species, with the N uptake demand of tomato, along with an increase in the overall soil N pool and N cycling [218].…”
Section: System Diversification To Improve Nuementioning
confidence: 99%
“…), which have a deep and branched taproot and grow relatively quickly to cover the soil and control weeds [18], can also be used as part of other cereal-legume combinations. Mixtures with the right ratio of legume to cereal can guarantee a low residue C: N ratio, which is fundamental for N to be available to the cash crop, especially in situations with slow mineralization rates such as in no-till systems [21,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Compost is environmentally neutral, according to the libraries used in the LCA study. Although some studies report that compost application increases soil carbon sequestration in row crops in California (Tautges et al, 2019; White et al, 2020) [3,4], the amount of soil carbon sequestration varies by crop system, which makes it difficult to generalize to other crop systems. Our LCA study is based on the environmental effects of the inputs and processes reported in the libraries of SimaPro.…”
mentioning
confidence: 99%